(untitled) (Research, Society and Development, 2021)
The objective of this study was to perform endodontic follow-up, through clinical and radiographic observation, or the type of treatment used, to identify groups of teeth that were used, to verify the cases of inappropriate use, to use the first attempts of endodontic treatment, to raise the type of intracanal medication that was used, survey which solutions and techniques of irrigated instrumentation used, quality of radiographs, quality of filling and use of endodontically used teeth were restored and which were lost. One hundred medical records of patients who underwent endodontic treatment at the dental clinic were selected. It was possible to perform a clinical and radiographic proservation of 44 teeth, of which 30 were incisors and 14 premolars. The radiographs were evaluated by two calibrated endodontists. The results shown for all teeth were classified as having satisfactory treatment quality. Regarding the filling limit, no overfilled or underfilled teeth were found, all (n = 100) were filled at the limit of the cementum dental canal (CDC). Regarding the condensation of the material obtained, all teeth (100%) were adequately condensed, observed by the radiopacity of the obtained on the radiography. Regarding the type of treatment most applied to necropulpectomy, in 96 teeth with injury (78.57%) and 4 teeth without injury (14.28%). Only 1 biopulpectomy (7.15%) was performed. Regarding intracanal medication, calcium hydroxide was used in almost all cases, caliber with PMCC (35.71%) and caliber (28.57%) followed by formocresol (21.42) and otosporin (7.15%), sodium hypochlorite was used in all cases (100%). Regarding masticatory function, 80 (85.71%) were restored with composite resin, 10 with part of a fixed bridge (7.15%) and 10 were fractured (7.15%). It can be concluded that most teeth are clinically and radiographically involved in endodontic treatment, including periapical regression.